2017
DOI: 10.1039/c7ra10604a
|View full text |Cite
|
Sign up to set email alerts
|

Direct cryopreservation of adherent cells on an elastic nanofiber sheet featuring a low glass-transition temperature

Abstract: Electrospun nanofibers, featured a lower glass-transition temperature than the freezing temperature and a loose mesh structure, allows the direct cryopreservation of adherent cells towards the investigation of cell-material composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
(35 reference statements)
1
26
0
7
Order By: Relevance
“…Interestingly, after 7 days of 3D paper‐based cell culture, followed by freezing for 2 days at −80 °C, and finally thawing; experiments showed integrity and survival of cells (Figure S8b, Supporting Information). Obviously, and along with previously published reports on various scaffold‐based cell cryopreservations,8,9,27,28 paper‐based cryopreservation additionally overcomes the obstacles related to cryopreserving precultured (i.e., adherent) cells on 3D porous environments; namely intracellular crystallization, dehydration injury, mechanical ruptures, and uneven cooling during the freeze.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, after 7 days of 3D paper‐based cell culture, followed by freezing for 2 days at −80 °C, and finally thawing; experiments showed integrity and survival of cells (Figure S8b, Supporting Information). Obviously, and along with previously published reports on various scaffold‐based cell cryopreservations,8,9,27,28 paper‐based cryopreservation additionally overcomes the obstacles related to cryopreserving precultured (i.e., adherent) cells on 3D porous environments; namely intracellular crystallization, dehydration injury, mechanical ruptures, and uneven cooling during the freeze.…”
Section: Discussionmentioning
confidence: 88%
“…[ 64 ] A direct comparison of cell recovery and attachment on polymeric meshes varying in T g and fiber orientation revealed that cell recovery of adherent mouse C2C12 myoblasts could be enhanced using scaffolds composed of fibers of low‐ T g polymers oriented in a random instead of aligned manner. [ 65 ] Both characteristics enabled cells to remain (more) attached even upon dehydration during freezing. Scaffolds of polymers with a T g below the freezing temperature of the cryopreservation medium (approximately −20 °C for medium supplemented with 10% DMSO) remain more elastic.…”
Section: Cryopreservation Of Cardiac Samplesmentioning
confidence: 99%
“…Indeed, cell adhesions were found to persist after cryopreservation for random meshes, whereas cell detachment occurred especially parallel to the long fiber axis of aligned (and tensioned) fiber meshes. Scaffolds composed of low‐ T g polymers (of sufficiently low molecular weight), such as polyurethane (PU; T g −40 °C) [ 65 ] or PCL ( T g −60 °C), [ 63 ] or mixtures of low‐ and high‐ T g polymers, such as PCL/CS and SPCL meshes, are thus preferred over aligned meshes formed from high‐ T g polymers such as polystyrene (PS; T g 106 °C), [ 65 ] so that the mesh remains in a rubbery and deformable state while the cells shrink during freezing of the culture medium after which further cooling to storage temperatures below the T g induces an increase in stiffness and possibly crystallinity of the scaffold material.…”
Section: Cryopreservation Of Cardiac Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2012), electrospun-polyurethane nanofiber sheets (Batnyam et al, 2017), alginate-gelatin cryogel sponges (Katsen-Globa et al, 2014), and reticulated polyvinyl formal resins (Miyoshi et al, 2010). The results of these studies proved that the biocompatibility, mechanical support, and 3D porosity of scaffolds provide a suitable balance in creating a protective microenvironment for the cells during their cryopreservation.…”
mentioning
confidence: 98%